Did the alien calycophoran Muggiaea atlantica outcompete its native congeneric M. kochi in the marine lakes of Mljet Island (Croatia)?. (17th February 2013) - Batistić, Mirna; Lučić, Davor; Carić, Marina; Garić, Rade; Licandro, Priscilla; Jasprica, Nenad
Abstract: The calycophoran siphonophore Muggiaea atlantica was recorded for the first time in the marine lakes of Mljet Island (South Adriatic) in 2001. The presence of M. atlantica in such semi‐enclosed environments provided a unique opportunity to describe its life cycle based on in situ observations of the annual variability of its asexual nectophore stage, sexual eudoxid stage (produces gonophores) and calyconula larvae. Muggiaea atlantica was present the whole year in the Malo jezero (Small Lake, SL), where it was actively reproducing between May and September 2001, with a maximum density of gonophores in May (141 gonophores m −3 ) and nectophores and larvae in June (37 nectophores m −3 and 80 larvae m −3 ). Higher temperatures below the thermocline (average 14.5–15.6 °C), and the availability of prey (e.g. small copepods, chaetognaths and bivalve larvae) were the main environmental factors related to successful reproduction of M. atlantica in SL. In the Veliko jezero (Great Lake, GL) nectophores and gonophores of M. atlantica were found in low numbers, mainly in the upper 20 m, between September and November 2001 and no larvae were recorded. In 2001, Muggiaea kochi, the sole calycophoran siphonophore previously reported in the GL, was not recorded in the Mljet lakes. We hypothesize that the cold (<13 °C) conditions over winter of 2000/2001 were not suitable for the warm‐temperate M. kochi and may have favoured its cold‐temperate congener, M. atlantica, which has progressively colonized the southern Adriatic since the mid‐1990s.